New interconnection networks: Fibonacci Cube and Extended Fibonacci Cubes based hierarchic networks - Karci, A (Ieee Computer Soc, 2001)
Chose et al developed interconnection networks which use hypercubes as basic building blocks and Duh et al used folded hypercubes as basic building blocks to construct interconnection networks. We used Fibonacci Cube and Extended Fibonacci Cubes as basic building blocks to construct new hierarchic interconnection networks. The obtained interconnection networks are better than the Fibonacci Cube and Extended Fibonacci Cubes with respect to average edge connectivity. They are also better than hypercube and Hierarchical Cubic Network with respect to costs of networks.
15th International Conference on Information Networking (ICON-15) -- JAN 31-FEB 02, 2001 -- BEPPU, JAPAN
Keywords: hierarchical interconnection networks; Fibonacci Cubes; Extended Fibonacci Cubes; hypercubes; interconnection networks